In Silico Identification of Novel Biomarkers and Development of New Rapid Diagnostic Tests for the Filarial Parasites Mansonella perstans and Mansonella ozzardi - C. B. Poole (Nature Portfolio, 2019)
Abstract Mansonelliasis is a widespread yet neglected tropical infection of humans in Africa and South America caused by the filarial nematodes, Mansonella perstans, M. ozzardi, M. rodhaini and M. streptocerca. Clinical symptoms are non-distinct and diagnosis mainly relies on the detection of microfilariae in skin or blood. Species-specific DNA repeat sequences have been used as highly sensitive biomarkers for filarial nematodes. We have developed a bioinformatic pipeline to mine Illumina reads obtained from sequencing M. perstans and M. ozzardi genomic DNA for new repeat biomarker candidates which were used to develop loop-mediated isothermal amplification (LAMP) diagnostic tests. The M. perstans assay based on the Mp419 repeat has a limit of detection of 0.1 pg, equivalent of 1/1000th of a microfilaria, while the M. ozzardi assay based on the Mo2 repeat can detect as little as 0.01 pg. Both LAMP tests possess remarkable species-specificity as they did not amplify non-target DNAs from closely related filarial species, human or vectors. We show that both assays perform successfully on infected human samples. Additionally, we demonstrate the suitability of Mp419 to detect M. perstans infection in Culicoides midges. These new tools are field deployable and suitable for the surveillance of these understudied filarial infections.